SAT0172 Osteoporosis prophylaxis in patients receiving corticosteroids. (1st June 2001) - Davies, RJ; Walton, T; Carulli, M; Kingsley, G; Hajela, V
Abstract : Background: Approximately 2% of all general medical outpatients are taking corticosteroids. 1 The link between corticosteroid consumption and osteoporosis with subsequent fracture is strong 2 and national guidelines have been drawn up for the prevention of corticosteroid induced osteoporosis (CSIO). 3 Objectives: To determine by means of re-audit whether management of CSIO improved following two education sessions and the distribution of guidelines to all general medical physicians, after the initial audit in July 1997. Methods: The standard used was the National Osteoporosis Society (NOS) guidelines for the management of CSIO. The notes of all patients attending rheumatology, gastroenterology and respiratory clinics at University Hospital Lewisham during July 1997 for the initial audit and April and May 2000 for the re-audit were examined. Education and guidelines about CSIO were given to all relevant departments and a re-audit undertaken 2 years later. Results: HIGH RISK GROUPS; age > 65 years and on > 7.5 mg/d prednisolone or < 65 years and on > 15 mg/d prednisolone. Initial audit 67% (57/85) were in this group, 5.2% had lifestyle advice, 15.7% BMD and 43.8% were prescribed prophylaxis. Re-audit 46.2% (37/80) were in this group, 24.3% had lifestyle advice, 51.3% BMD and 67.6% were prescribed prophylaxis. MEDIUM RISK GROUPS; age < 65 years, prednisolone dose > 7.5 mg/d <15 mg/d. Initial audit 7% (6/85) were in this group, 16.6% had lifestyle advice, 50% BMD and 66.6% were receiving prophylaxis. Re-audit 32.5% (26/80) were in this group, 30.8% had lifestyle advice, 50% BMD and 42.3% were receiving prophylaxis. LOW RISK GROUPS; prednisolone < 7.5 mg/d. Initial audit 25.8% (22/85) were in this group, none had received lifestyle advice, 22.7% BMD and 27.2% were receiving prophylaxis. Re-audit 21.2% (17/80) were in this group, none received lifestyle advice, 23.5% BMD and 52.9% were receiving prophylaxis. Conclusion: Education and distribution of NOS guidelines lead to an increase in the number of high risk patients receiving appropriate treatment. The percentage of patients receiving prophylaxis in July 1997 was 41.1% and 56.2% in the re-audit. Clarity is needed in the management of low risk groups. Patients receiving lifestyle advice remains unacceptably low. There is a reluctance to prescribed calcium and vitamin D to medium risk patients and those awaiting DEXA scan results. References: Bell R, Carr A, Thompson PW. Managing corticosteroid induced osteoporosis. J R Coll Phys. 1997;31:158–61 American College of Rheumatology Task Force on Osteoporosis Guidelines. Recommendations for the prevention and treatment of glucocorticoid induced osteoporosis. Arthritis Rheumatol. 1996;39:1791–801 Eastell R, et al . A UK Consensus Group on management of glucocorticoid induced osteoporosis: an update. J Intern Med. 1998;244:271–92